Spatial distribution and clustering of the proportion of disabled individuals by districts in Punjab - Masood Ali Shaikh (Journal of the Pakistan Medical Association, 2023)
Disabilities are globally endemic and will increase with population ageing and ubiquitous prevalence of noncommunicable diseases. The Pakistan Social and Living Standards Measurement survey conducted in 2019-20 is the only district-level representative survey that provides proportion of disabled individuals. The survey used a standardized and validated six-questions from the ‘Washington Group Questions’ that identify functional disabilities pertaining to difficulty in the domains of sight, hearing, walking/climbing steps, remembering/ concentrating, self-care (washing/dressing), and communicating/being understood. Disabilities were more common in men in both urban and rural areas of districts. Continue...